A taxonomic overview and key to the ants of Barrow Island, Western Australia - Heterick, Brian E. (Western Australian Museum, 2013)
This work characterises the ant (Hymenoptera: Formicidae) fauna of Barrow Island, Western Australia, and provides a key to the workers and several unique reproductives of the 117species recorded from the island thus far. In all, 11 of the 13 subfamilies of Western Australian ants have been recorded from Barrow Island, but Myrmeciinae and Heteroponerinae are absent. At a generic level, the fauna of the island is less rich, holding 36 of the 71 genera currently known from Western Australia. The ant fauna is characteristic of the Eremae a Botanical Province of the Pilbara, rather than that of the Carnarvon Basin from which Barrow Island is geologically derived. Ninety-three ant species (79.5% of the total on Barrow Island) are shared with the ant fauna of the Pilbara region on the adjoining mainland, but only 52 species (44.4% of the total) are shared with the ant fauna of the Carnarvon Basin. The island is very rich in unspecialised and thermophilic ant species. Five such genera, i.e., Iridomyrmex (14 spp.), Monomorium (13 spp.), Polyrhachis (12 spp.), Melophorus (10spp.), and Camponotus (nine spp.) make up almost 50% (i.e., 49.6%) of the island’s ant fauna. Very few ants appear to be endemic to Barrow Island. The relative proportions of the two major subfamilies(Formicinae and Myrmicinae, together comprising 61.5% of the total ant richness) are similar to the proportions found in the South-west Botanical Division for these two subfamilies (i.e., 65.9%), with Barrow Island having a slightly lower ratio of formicines to myrmicines than is found in the south-west of the state. An estimate of the total number of ant species likely to occur on Barrow Island, using the Estimate-S program (Colwell 2009), suggests that a maximum of fourteen additional species may be as yet unrecorded.